2023
DOI: 10.1111/ele.14324
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization alters the spatiotemporal dynamics of plant–pollinator networks in a tropical megacity

Gabriel Marcacci,
Catrin Westphal,
Vikas S. Rao
et al.

Abstract: Urbanization is a major driver of biodiversity change but how it interacts with spatial and temporal gradients to influence the dynamics of plant–pollinator networks is poorly understood, especially in tropical urbanization hotspots. Here, we analysed the drivers of environmental, spatial and temporal turnover of plant–pollinator interactions (interaction β‐diversity) along an urbanization gradient in Bengaluru, a South Indian megacity. The compositional turnover of plant–pollinator interactions differed more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This pattern can be explained by the generalist nature of the pollinator communities and suggest that, in our study system, the composition of local pollinator communities is more affected by the local species pool and the surrounding matrix composition than by the local plant community (Öckinger et al, 2012;Steffan-Dewenter, 2003). Given that the pollinator communities were not nested and connectivity was not related to species richness, dispersal limitation likely only had a minor effect on spatial turnover, whereas environmental factors such as the surrounding matrix may have a larger impact (Cusser et al, 2018;Marcacci et al, 2023). However, we did find a significant correlation between plant and pollinator community dissimilarities, but this effect disappeared when geographic distance was corrected for, indicating that this was most likely the result of both communities experiencing a similar rate of distance decay (Graco-Roza et al, 2022).…”
Section: Nestedness and Species Turnovermentioning
confidence: 80%
“…This pattern can be explained by the generalist nature of the pollinator communities and suggest that, in our study system, the composition of local pollinator communities is more affected by the local species pool and the surrounding matrix composition than by the local plant community (Öckinger et al, 2012;Steffan-Dewenter, 2003). Given that the pollinator communities were not nested and connectivity was not related to species richness, dispersal limitation likely only had a minor effect on spatial turnover, whereas environmental factors such as the surrounding matrix may have a larger impact (Cusser et al, 2018;Marcacci et al, 2023). However, we did find a significant correlation between plant and pollinator community dissimilarities, but this effect disappeared when geographic distance was corrected for, indicating that this was most likely the result of both communities experiencing a similar rate of distance decay (Graco-Roza et al, 2022).…”
Section: Nestedness and Species Turnovermentioning
confidence: 80%
“…Data are available via the Dryad Digital Repository https://doi.org/10.5061/dryad.0vt4b8h4d (Marcacci et al, 2023).…”
Section: Peer Reviewmentioning
confidence: 99%
“…However, organisms live in spatial communities (Torres-Pulliza et al, 2020) and empirical work is reinforcing the importance of heterogeneous networks of interaction and replacement in shaping the genetic makeup of eco-evolutionary systems. Spatial and temporal gradients have been shown to interact to shape the dynamics of plant–pollinator networks (Marcacci et al, 2023) and the complex branching topology of riverine ecosystems has been shown to be critical for biodiversity maintenance (Terui et al, 2021). Wastewater networks have been shown to harbor complex spatial ecosystems of critical importance for human health due to their potential to harbor antibiotic resistance gene-carrying bacteria (Medina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%